(untitled) - Henssen, J. L. G. (The Netherland, 1996)
Administrative, social and legal aspects of Land Registration / cadastre includes 8 chapter. Chapter 1: Introduction. Chapter 2: Location of landregistration and cadastre in LIS. Chapter 3: Land recording. v.v...
Keywords: Land management,Quản lý đất đai